2008
DOI: 10.1007/s10522-008-9130-1
|View full text |Cite
|
Sign up to set email alerts
|

Forty percent and eighty percent methionine restriction decrease mitochondrial ROS generation and oxidative stress in rat liver

Abstract: Dietary restriction (DR) lowers mitochondrial reactive oxygen species (ROS) generation and oxidative damage and increases maximum longevity in rodents. Protein restriction (PR) or methionine restriction (MetR), but not lipid or carbohydrate restriction, also cause those kinds of changes. However, previous experiments of MetR were performed only at 80% MetR, and substituting dietary methionine with glutamate in the diet. In order to clarify if MetR can be responsible for the lowered ROS production and oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 60 publications
9
81
1
Order By: Relevance
“…A trend for a lower CII content was also found in long-lived strains of drosophila (Neretti et al, 2009). More strikingly, a 40% or 80% methionine restriction in rats both increased longevity and decreased CII content to a greater extent than the decreases found for any other complexes of the ETS (Caro et al, 2008). Although few in number, these studies clearly suggest that it may be worth investigating CII content in relation to longevity in future studies.…”
Section: Mechanisms For Reduced Hydrogen Peroxide Production Ratementioning
confidence: 58%
See 1 more Smart Citation
“…A trend for a lower CII content was also found in long-lived strains of drosophila (Neretti et al, 2009). More strikingly, a 40% or 80% methionine restriction in rats both increased longevity and decreased CII content to a greater extent than the decreases found for any other complexes of the ETS (Caro et al, 2008). Although few in number, these studies clearly suggest that it may be worth investigating CII content in relation to longevity in future studies.…”
Section: Mechanisms For Reduced Hydrogen Peroxide Production Ratementioning
confidence: 58%
“…CI content is also reduced in rat mitochondria after diet restriction treatments (Ayala et al, 2007;Caro et al, 2008). Complex I is known to be a major contributor to ROS production.…”
Section: Mechanisms For Reduced Hydrogen Peroxide Production Ratementioning
confidence: 98%
“…Diets high in protein or amino acids could push cells into oxidative stress by increasing ROS production from the mitochondria, impairing antioxidant defences against ROS or reducing the repair of oxidised molecules (López-Torres and . In support of this idea, in rats, reduced intake of both protein and amino acids reduces oxidative damage (Ayala et al, 2007;Caro et al, 2008;Sanz et al, 2004Sanz et al, , 2006). This appears to be because dietary manipulation lowers ROS production during electron transport in the mitochondria, both by reducing the concentration of mitochondrial respiratory complexes that generate ROS and also by changing the degree of electronic reduction of these complexes (the greater the level of reduction, the more ROS are produced) (Sanz et al, 2006).…”
Section: Introductionmentioning
confidence: 89%
“…It has been demonstrated in a number of models that caloric restriction decreases mitochondrial free radical generation thus decreasing macromolecule and mitochondrial damage (Barja, 2004). Interestingly restriction of methionine intake (40% and 80% restriction) has also been shown to decrease mitochondrial ROS generation and percent free radical leak in rat liver mitochondria (Caro et al, 2008). The same group also reported that protein restriction alone could decrease mitochondrial ROS production and mtDNA damage in rat liver (Sanz et al, 2004).…”
Section: Ros and Agingmentioning
confidence: 96%